IMPLEMENTASI GOOD GOVERNANCE DALAM PROSES REKRUTMEN APARATUR SIPIL NEGARA DI BADAN KEPEGAWAIAN DAERAH KOTA MANADO - TUTU, VETI; LALOMA, ALDEN; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2016)
Abstract: this research was conducted by focusing the discussion on the issue of the implementation of goodgovernance in the process of Staffing of the Agency's employees in the rekruitment area of the city ofManado. This research aims to find out how the implementation of good governance in the process ofrekruitment of the civil State apparatus in manado City area staffing agency.The research was conducted using qualitative research methods to explore and build a preposition or explainthe meaning behind the reality of regional Staffing Agency in Manado city with number of respondents asmuch as 5 employees. The techniques used to conduct the data collection is the observation, interviews, anddocumentation. Technique of data analysis used in qualitative research is a model, Miles and Huberman.Based on research done then it is known that there is a good and clear communication regarding the processof Staffing of the Agency's employees in the rekruitment area of the city of Manado; the availability ofresources that support such as HUMAN RESOURCES and means as well as infrastructure in therekruitment employees; the level of honesty and commitment to employee-owned well enough; as well as thebureaucratic structure that is not such a convoluted process of rekruitment which made online to anticipategoing wild charges, already felt good. In terms of transparency and accountability in the process ofrekruitment has been very good but there are still some things that need to be enhanced to further improvethe quality of existing employees.Keywords: Implementation, Good Governance, Regional Staffing Agency